The corporate income tax effect of group restructurings in South Africa - Blew, Candyce (My University, 2016)
Due to the vast number of groups of companies having many subsidiaries that are no longer viable from an economic perspective or that no longer gain the tax benefit that they were first created to achieve, there are many group restructurings occurring. These restructurings are to potentially simplify the group structure as well as achieve the maximum tax benefit. This research report will analyse how groups may be restructured in line with the provisions of the Income Tax Act (‘the Act’) as it stands currently by looking back at how restructurings were dealt with in the past and how that has now evolved. The research discusses the corporate rollover relief provisions that may be applied in order to simplify the restructuring process which is commonly used in today’s practice. The research suggests that there are many different ways to restructure a group in order to gain the maximum amount of benefit from a tax perspective. Key Words: branch, capital gains tax (CGT), corporate income tax, corporate rollover relief, deregistration, foreign tax resident, general anti-avoidance rules (GAAR), liquidation, partnership, restructure, value-added tax.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specializing in Taxation) Johannesburg 2015
Keywords: Capital gains tax; CGT; Corporate income tax; Corporate rollover relief; Deregistration; General anti-avoidance rules (GAAR); Liquidation; Restructure; Value-added tax